The Evaluation Of Tahfiz Quran Learning Program In Integrated Islamic Elementary School (Sdit) Dod Deli Serdang - Abd Rahman; Fakhruddin Fakhruddin; Mesiono Mesiono (Proceeding International Seminar of Islamic Studies, 2019)
An evaluation of the implementation of the tahfiz Quran learning program is needed which can be reviewed from all aspects in a comprehensive manner, both in terms of program needs, program inputs, program processes and outputs of the learning program. Therefore, this study aims to evaluate the tahfiz Quran learning program through the CIPP (Context, Input, Process and Product) evaluation model that focuses on a number of core questions namely related to context conditions, input conditions, process conditions, and product conditions of the tahfiz Quran learning program. This research was conducted at the Integrated Islamic Elementary School SDIT DOD Deli Serdang under the auspices of the Indonesian Integrated Islamic School Network (JSIT). This research method uses qualitative research methods, data collection is done by interviewing techniques, observation, and document study with CIPP evaluation analysis (context, input, process and product). The results of this study are:The condition of the context of the tahfiz Quran learning program at SDIT DOD Deli Serdang was considered very good. This is seen from the aspects of support, program needs and needs for the program and program objectives. Thus it can be recommended that from the aspect of the context of the tahfiz Quran learning program at SDIT DOD Deli Serdang can be continued. At the input condition it is concluded with sufficient value. This is reviewed in terms of eligibility on human resources criteria, implementation budget criteria, infrastructure criteria, and on the learning program procedure criteria. Researcher's recommendations on input aspects of the tahfiz Quran learning program at Deli Serdang DOD SDIT can be forwarded to important notes needing improvements. In the condition of the process it was found that the process of implementing the tahfiz Quran learning program with the specified criteria got sufficient. Then the recommendation of this study is that from the aspect of the process of the tahfiz Quran learning program in SDIT DOD Deli Serdang forwarded to the improvements. The condition of the product, this study found that the aspects of the competence of the tahfiz Quran with less value and on the criteria of noble morals and good deeds with very good value. Thus it can be recommended that from the product aspect of the tahfiz Quran learning program at SDIT DOD Deli Serdang be continued by improvements.